Gasified olive stone biochar as a green construction fill material - Bai, Yueji (2024)
The rapid growth in biomass waste generation from industrial and agricultural sectors has emerged as a significant global challenge. One potential solution to address this challenge is to utilize biomass waste materials as sustainable construction materials, which can mitigate landfilling concerns, reduce the need for natural materials and ultimately minimize carbon emissions. This study focused on the evaluation of the engineering and environmental properties of olive stone biochar (OSB) as a green construction fill material. OSB is the solid residue resulting from biomass gasification in a waste-to-energy plant. The properties of OSB were compared to those of recycled glass (RG), a mainstream construction and demolition (C&D) waste material in Australia, for benchmarking purposes. Extensive laboratory tests were conducted on unbound OSB, RG and OSB/RG blends. The results indicated that gasified OSB was a stable biomass material and it exhibited good engineering performance when used as a construction fill material. In cases where higher strength was required, OSB can be blended with RG to achieve higher values of California bearing ratio (CBR) and resilient modulus. All OSB/RG blends were found to meet the minimum CBR requirement for subgrade materials as specified by the local road authority. Environmental tests revealed that the application of OSB as a construction fill material would not have any adverse environmental impact. This research highlighted the potential for OSB to replace virgin quarry materials in geotechnical fill and road subgrade applications. The involvement of biochar as a carbon sink in construction works also aligns well with the strategy to manufacture green materials within the construction industry, as it serves the dual purpose of locking carbon in a stable state within infrastructures and boosting waste reutilization rates simultaneously.